2016
DOI: 10.19139/soic.v4i1.167
|View full text |Cite
|
Sign up to set email alerts
|

A cubic B-spline Galerkin approach for the numerical simulation of the GEW equation

Abstract: The generalized equal width (GEW) wave equation is solved numerically by using lumped Galerkin approach with cubic B-spline functions. The proposed numerical scheme is tested by applying two test problems including single solitary wave and interaction of two solitary waves. In order to determine the performance of the algorithm, the error norms L 2 and L∞ and the invariants I 1 , I 2 and I 3 are calculated. For the linear stability analysis of the numerical algorithm, von Neumann approach is used. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The three invariants in this case are tabulated in Table (7) . It is clear that the quantities are satisfactorily constant and very closed with the methods [8,31,32] during the computer run. Fig.…”
Section: Interaction Of Two Solitary Wavesmentioning
confidence: 94%
See 3 more Smart Citations
“…The three invariants in this case are tabulated in Table (7) . It is clear that the quantities are satisfactorily constant and very closed with the methods [8,31,32] during the computer run. Fig.…”
Section: Interaction Of Two Solitary Wavesmentioning
confidence: 94%
“…The error aberration varies from −8×10 −2 to 1 × 10 −2 and the maximum errors happen around the central position of the solitary wave. For our second experiment, we take the parameters p = 3, c = 0.3, h = 0.1, ∆t = 0.2, ε = 3, µ = 1, x 0 = 30 with interval [0, 80] to coincide with that of previous papers [8,31,32]. Thus the solitary wave has amplitude 1.0 and the computations are carried out for times up to t = 20.…”
Section: Propagation Of Single Solitary Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gardner et al [5] showed the existence and uniqueness of solutions of the KdV equation. Many researches have used various numerical methods including finite difference method [6,7], finite element method [8][9][10][11][12][13][14][15][16][17][18], pseudospectral method [3] and heat balance integral method [19] to solve the equation. MKdV equation is a special case of the generalized Korteweg de-Vries (GKdV) equation having the form…”
Section: Introductionmentioning
confidence: 99%